A novel GPR-based prediction model for cyclic backbone curves of reinforced concrete shear walls. (15th March 2022) - Deger, Zeynep Tuna; Taskin, Gulsen
Abstract: Backbone curves are used to characterize nonlinear responses of structural elements by simplifying the cyclic force–deformation relationships. Accurate modeling of cyclic behavior can be achieved with a reliable backbone curve model. In this paper, a novel machine learning-based model is proposed to predict the backbone curve of reinforced concrete shear (structural) walls based on key wall design properties. Reported experimental responses of a detailed test database consisting of 384 reinforced concrete shear walls under cyclic loading were utilized to predict seven critical points to define the backbone curves, namely: shear at cracking point ( V cr ); shear and displacement at yielding point ( V y and δ y ); and peak shear force and corresponding displacement ( V max and δ max ); and ultimate displacement and corresponding shear ( V u and δ u ). The predictive models were developed based on the Gaussian Process Regression method (GPR), which adopts a non-parametric Bayesian approach. The ability of the proposed GPR-based model to make accurate and robust estimations for the backbone curves was validated based on unseen data using a hundred random sampling procedure. The prediction accuracies (i.e., ratio of predicted/actual values) are close to 1.0, whereas the coefficient of determination ( R 2 ) values range between 0.90–0.97 for all backbone points. The proposed GPR-based backbone models are shown to reflect cyclic behavior more accurately than the traditional methods, therefore, they would serve the earthquake engineering community for better evaluation of the seismic performance of existing buildings. Highlights: Predictive models are developed for nonlinear behavior (backbone) of RC shear walls. Backbone curve points are associated with yielding, peak shear, and peak deformation. The GPR method is utilized to model backbone curves in terms of wall properties. Accurate predictions ( R 2 > 0 . 90 ) are observed based on the proposed GPR-based models.